Antecedent of Corporate Entrepreneurial Orientation on the Performance of Small and Medium Manufacturing Enterprises in the Post Covid 19 Era: The Case Nigeria - Muazu, Muazu Hassan; Shehu Yahaya, Usman (Journal of Technology Management and Business, 2022)
Even in the post-pandemic period, the Covid-19 pandemic still has a multiplier effect on the performance of SMEs. As sales revenues dropped, branches were closed, and employees’ jobs and overall performance were impacted negatively around the world. This paper aims to review literature to determine research antecedents on the relationship between firms’ entrepreneurial orientation and manufacturing SMEs' performance in the post-Covid-19 era in Africa and the rest of the developing economies. This is to note the area needed to cover some of the major causes of the variation in this sub-sector of the economy for future research. A literature survey methodology was employed for the current article. Articles were reviewed from sources including journals (Google Scholar, ScienceDirect, Academia, and ResearchGate platform), and ordinary articles that spanned from 2002-2022 to understand the antecedents of research contexts and variables explored. The findings revealed that most studies focused on large-scale manufacturing firms and SMEs and considered external environmental factors like regulation, competition, interest and a few others to explain variation in enterprise performance. Furthermore, the result shows that non-multidimensional measures of enterprise performance were used. Consequently, a new conceptual framework was developed to look at firms’ inward entrepreneurial orientation as the driving factor for organisational performance improvement. The implication of the proposed framework developed is to harness strategies for performance improvement, growth, and survival in a complex and dynamic business environment. Thus, the paper concludes that the way to this development is for SMEs to build capacities that entrench their corporate entrepreneurial orientation to suit every business situation.